Ambient temperature and ruptured abdominal aortic: a retrospective study from Bosnia and Herzegovina - Muhamed Djedović; Armin Sljivo; Bedrudin Banjanovic; Haris Vukas; Edin Kabil; Alden Begic; Samed Djedović (Medicinski glasnik, 2026)
Introduction: Ruptured abdominal aortic aneurysm (RAAA) is a life-threatening emergency with high mortality. While conventional risk factors are well recognized, emerging evidence suggests environmental temperature may also influence rupture risk. This relationship has not been studied in Bosnia and Herzegovina. The aim of this study is to investigate the association between ambient temperature and RAAA incidence. Methods: A retrospective observational study was conducted at the Clinical Center of the University of Sarajevo between January 2021 and February 2025. Data from 105 RAAA patients were analyzed using demographic, clinical, and temperature data, with time series analysis assessing patterns around rupture events. Results: The mean patient age was 71.5 ± 7.6 years; 86.7% were male. The average aneurysm diameter was 85.1 ± 17.7 mm. Hypertension (68.6%), smoking (55.2%), and diabetes (37.7%) were the most prevalent comorbidities. The mortality rate was 38.7%. Most ruptures occurred during colder months, with a peak in January (16.1%) and a low in August, March, and February (each 4.7%). The mean ambient temperature during the 10 days before rupture was 11.41 ± 6.16 °C, not significantly different from the temperature on the rupture day (p = 0.991). However, minimum daily temperature was significantly lower than the mean daily temperature on rupture days (6.48 ± 5.92 °C vs. 11.42 ± 17.61 °C; p < 0.001). Conclusion: A seasonal RAAA pattern with winter clustering was observed, but no consistent short-term link to ambient temperature was found, warranting further study with advanced models.
Keywords: Abdominal aortic aneurysm; aortic rupture; cardiovascular diseases; temperature; seasons